Construction of Russian exceptionalism: first Orientologists in Russian academia - Demirtaş, Melih (Cappadocia Journal of Area Studies, 2020)
Since the exact place of Russian state and society between “the East” and “the West” has been a contested topic for ages, “Russian Orientalism” has also turned to be one of the key words in the Russia and Eurasia-related area studies. In this paper, one source of this "Orientalism" is searched in the so-called “Russian exceptionalism” or “uniqueness”. Thus, first supportive arguments are tried to be found in Russian Academia in the 19th century, through which a growing impact of Orientologists led to the ideas in line with the official circles of Russian imperialism. It will be therefore argued that supported from the Academia’s works increasingly, the effect of “spatiality” appeared as “in-between status” has provided a more hegemonic and stronger Russian mentality nurtured from both similarities and/or contrasts with both Western and Eastern neighbors. One strong argument will remain however as a current evaluation: the “civilized” Russian central elites have continued to search their State’s “Orient” always within the “eastern” territories conquered, like in the Caucasus, Idel/Volga or in Central Asia (Turkestan).